Research on the Spatial-Temporal Coupling Effect of Industrial Structure Upgrading and Human Resources in Western China - Meng, Tian (Wireless communications and mobile computing, 2022)
Industrial development and human resources matching can better promote economic growth. The mismatch, incoordination, and noninteraction between the upgrading of the industrial structure and human resources in the western region have severely restricted the speed and quality of regional economic development. Based on the in-depth analysis of the coupling effect mechanism of industrial structure upgrading and human resources in the western region, this paper constructs an evaluation index system for industrial structure upgrading and human resources in the western region. The coupling coordination degree model was used to calculate and analyze the coupling degree and coupling coordination degree between the industrial structure upgrading and human resources in western China. The results show that from 2009 to 2018, the industrial structure upgrade and the level of human resources in the western regions continued to rise. Before 2015, the level of industrial structure was higher than the level of human resources, and then the opposite trend appeared. From the perspective of regional distribution, the coupling and coordination of the two systems in western regions are quite different. The upgrading of industrial structure and the coordination of human resources in the three regions of Shaanxi, Chongqing, and Sichuan are generally higher than those in other regions, but there was still a gap from the high-quality coupling state. Therefore, an in-depth understanding of the coupling stage, current situation, and problems of industrial structure upgrading and human resources in western regions will help to further promote the high-quality economic development of western regions.